PENGARUH KEPEMIMPINAN AKADEMIK TERHADAP KINERJA DOSEN DALAM PERSPEKTIF MANAJEMEN ORGANISASI DI FAKULTAS BISNIS DAN HUMANIORA UNIVERSITAS TJUT NYAK DHIEN - Frensius Pasaribu, Donald (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of academic leadership on faculty performance at the Faculty of Business and Humanities, Tjut Nyak Dhien University, from the perspective of organizational management. Academic leadership is considered a strategic factor that not only determines the direction of institutional policies but also plays a crucial role in shaping organizational culture, motivation, and overall effectiveness. The research employed a quantitative approach using a survey technique, in which questionnaires were distributed to permanent lecturers and subsequently analyzed through multiple linear regression models. The findings reveal that academic leadership has a positive and significant effect on faculty performance, encompassing teaching, research, and community service. These results highlight that participative, visionary, and communicative leadership styles can enhance individual performance while simultaneously strengthening organizational capacity. The implications of this study underscore the importance of implementing organizational management practices grounded in academic leadership, oriented toward human resource development, to improve institutional competitiveness amid the dynamics of higher education.